Integration of BMP, Wnt, and Notch signaling pathways in osteoblast differentiation - Lin, Grace L. (2011)
Bone marrow-derived mesenchymal stem cells (MSCs) are multipotent progenitors that can commit to osteoblast, chondrocyte, adipocyte, and several other lineages. The proper utilization of stem cells for clinical applications requires an integrated understanding of multiple signal inputs that control maintenance of stemness, proliferation, commitment, and differentiation. Various signaling pathways have been implicated in the regulation of MSC differentiation; however, complexities of pathway interactions, as well as seemingly contradictory results in the literature, create an often confusing and disjointed knowledge base. Several recent publications explore the integration of signaling pathways such as BMP, Wnt, Notch, Hedgehog, and Fibroblast Growth Factors in MSC osteoblast differentiation. The transcription factor Cbfa1/Runx2 has been implicated in these pathways as a potential focal point for signaling integration. This review will outline the current understanding of these pathways and indicate where both spatiotemporal effects during differentiation and comparable experimental conditions need to be considered in order to clarify the outcome(s) of differing regulatory levels of these signaling pathways.